Heart rate-reducing therapy with add-on ivabradine and bisoprolol before coronary computed tomographic angiography in a fast-track ambulatory setting. Issue 6 (June 2018) - Muster, Viktoria; Wallner, Markus; Schmidt, Albrecht; Kapl, Martin; von Lewinski, Friederike; Rainer, Peter; Reittner, Pia; Tillich, Manfred; Brader, Peter; Szolar, Dieter HM; von Lewinski, Dirk
Objective: This study was performed to determine whether add-on oral ivabradine in patients treated with beta blockers 1 hour before coronary computed tomographic angiography (CCTA) is effective in lowering the heart rate and thus improving CCTA quality. Methods: In this single-center cohort study, the data of 294 patients referred for ambulant CCTA were retrospectively screened. Patients with an initial heart rate of ≥75 bpm (n = 112) were pretreated with either a combination of bisoprolol and ivabradine or with bisoprolol alone. Results: During the scan, there was no difference in heart rate between the two groups Likewise, there was no significant difference in additionally administered intravenous bradycardic agents, the number of motion artifacts, or the radiation dose. Both drug regimens were tolerated well. Conclusion: Additive oral ivabradine 1 hour before CCTA does not result in a further reduction of the heart rate. Consequently, neither movement artifacts nor radiation dose can be reduced. Therefore, pretreatment with ivabradine does not seem reasonably appropriate in an outpatient clinical setting with short patient contact.